If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -11 = 61 + -3x Reorder the terms: -11 + 6x = 61 + -3x Solving -11 + 6x = 61 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -11 + 6x + 3x = 61 + -3x + 3x Combine like terms: 6x + 3x = 9x -11 + 9x = 61 + -3x + 3x Combine like terms: -3x + 3x = 0 -11 + 9x = 61 + 0 -11 + 9x = 61 Add '11' to each side of the equation. -11 + 11 + 9x = 61 + 11 Combine like terms: -11 + 11 = 0 0 + 9x = 61 + 11 9x = 61 + 11 Combine like terms: 61 + 11 = 72 9x = 72 Divide each side by '9'. x = 8 Simplifying x = 8
| 13x+3=-23 | | y+8=28 | | 5x+12=3x+13 | | z+6=15 | | 3x+27=12x+13 | | 7x-2=6x+1 | | 360=127+53+127+-2+5x | | y/2=2 | | (-10x-7)-(3x-10)= | | (10x-7)-(3x-10)= | | 4b^3-12b^2-832b=0 | | 14y=126 | | 360=145+66+63+x+57 | | 3g-6=12 | | 3g-6=-12 | | 9x^2-72x-16y^2-3y-16=0 | | 15-z=1 | | 360=100+66+45+12x-7 | | Z+3x-2+z-5x+7= | | 4x/7-x | | 12(x+8)=8*30 | | sqrt(x+6-5)=0 | | y=1/4x^2-9 | | 585+.13x= | | 1/2.9.h=94.5 | | 2+13=30 | | ln(8x^2-5x+1)=0 | | 3x-9=3x-3 | | -196=7x+7(5x+14) | | 525+.21x= | | 1-(1-6m/7) | | (y^2x)*(y^2)-4(y^3)=0 |